Efficacy and safety of paliperidone palmitate 3-month formulation in Latin American patients with schizophrenia: A subgroup analysis of data from two large phase 3 randomized, double-blind studies - Savitz,Adam J. (2019)
Objective: To analyze the efficacy and safety of paliperidone palmitate 3-monthly (PP3M) in Latin American patients with schizophrenia vs. rest-of-world (ROW). Methods: We analyzed data from two multinational, double-blind (DB), randomized, controlled phase 3 studies including patients with schizophrenia (DSM-IV-TR) previously stabilized on PP1M/PP3M (open-label [OL] phase). Patients were randomized to PP3M or PP1M (noninferiority study A) and PP3M or placebo (study B) in DB phase. The subgroup analysis included Latin American (Argentina, Brazil, Colombia, Mexico) patients. Primary efficacy endpoints were relapse-free rates (study A) and time-to-relapse (study B). Results: In study A, 63/71 (88.7%) and in study B 38/43 (88.4%) Latin American patients completed the DB phase. In study A, relapse-free percentage was similar in Latin America (PP3M: 97%, PP1M: 100%) and ROW (PP3M: 91%, PP1M: 89%). In study B, median time-to-relapse was not estimable in the Latin American subgroup for either placebo or PP3M groups, nor for the ROW PP3M group; the median time-to-relapse in the ROW placebo group was 395 days. Caregiver burden improved in patients switching from oral antipsychotics (OL baseline) to PP3M/PP1M in DB phase (Involvement Evaluation Questionnaire score mean ± SD change, -9.4±15.16; p < 0.001). Treatment emergent adverse events with PP3M during DB phase were similar in Latin America (study A: 24/34 [70.6%]; study B: 15/21 [71.4%]) and ROW (study A: 318/470 [67.7%]; study B: 84/139 [60.4%]) subgroups. Conclusion: PP3M was efficacious and showed no new safety concerns in patients with schizophrenia from Latin America, corroborating ROW findings. Clinical trial registration: NCT01515423, NCT01529515